The Role of Communication in Building Tolerance and Unity in a Diverse Society: A Systematic Literature Review - Dharma, Yudi; Seneru, Wistina; Obi, Sabina Nwakaego (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
In the context of globalization, societies are increasingly diverse in culture, religion, language, and values. These differences can enrich interactions but also lead to misunderstanding and conflict. This study explores how communication can promote tolerance and unity in heterogeneous communities. A qualitative approach with a systematic literature review was used to analyze studies published in the last decade. The review identifies several key communication strategies: open dialogue, mutual listening, inclusive language, intercultural understanding, and responsible use of media. Empathic communication, respect for differing perspectives, and constructive conflict resolution also play crucial roles in fostering social cohesion. The findings suggest that communication is not only a means of sharing information, but a social tool for building trust, reducing prejudice, and strengthening unity. The study recommends collaboration among individuals, communities, and institutions to support inclusive and empathetic communication. These efforts are essential for developing policies, education systems, and media content that reflect and reinforce values of tolerance in diverse societies.